Should the first blood pressure reading be discarded? - Salazar, Martín R. (2015)
We evaluated the consequences of excluding the first of three blood pressure (BP) readings in different settings: a random population sample (POS, n=1525), a general practice office (GPO, n=942) and a specialized hypertension center (SHC, n=462). Differences between systolic and diastolic BP (SBP and DBP) estimates obtained including and excluding the first reading were compared and their correlation with ambulatory BP monitoring (ABPM) was estimated. The samples were divided into quartiles according to the difference between the third and the first SBP (3-1ΔSBP). SBP decreased through sequential readings, 3-1ΔSBP was -5.5 ± 9.7 mm Hg (P<0.001), -5.1 ± 10.4 mm Hg (P<0.001) and -6.1 ± 9.3 mm Hg (P<0.001) for POS, GPO and SHC, respectively. However, individuals included in the top quartile of 3-1ΔSBP showed their highest values on the third reading. The mean SBP estimate was significantly higher excluding the first reading (P<0.001), but the differences among both approaches were small (1.5-1.6 mm g). Moreover, the correlation between SBP values including and excluding the first reading and daytime ABPM were comparable (r = 0.69 and 0.68, respectively). Similar results were observed for DBP. In conclusion, our study does not support the notion of discarding the first BP measurement and suggests that it should be measured repeatedly, regardless the first value.